Pengaruh Person Organization Fit terhadap Turnover Intention melalui Person Job Fit sebagai Variabel Mediasi - Ayu Iqtiyah Arum (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
The decline in performance and productivity within the company is a negative impact that arises due to the high level of employee turnover intention. This study aims to analyze the direct impact of person-organization fit and person-job fit on turnover intention. This study further examines the mediating role of person-job fit. The research method uses a quantitative approach. The survey was conducted by distributing questionnaires to 68 employees of the production division of a manufacturing company branch. The data analysis technique uses structural equation modelling (SEM) with the SmartPLS 3.0 application program. and SPSS.25 applications program to analyze descriptive statistics. The results showed that person-organization fit had a positive and significant effect on person-job fit. Person organization fit has a negative and significant effect on turnover intention. Person job fit has no significant negative effect on turnover intention. Person job fit does not mediate the relationship between person-organization fit and turnover intention. The implication of this research is that employees have person-organization fit and person-job fit but have a high turnover intention, so companies need to integrate policies that are able to encourage person-organization fit and person-job fit to reduce employee desire to leave the company.